Perancangan Sistem Informasi Posyandu Berbasis Web Dengan Metode Extreme Programming Pada Desa Candinata - Aji, Briyan Gifari; Prasetyo, Muhamad Awiet Wiedanto (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
The advancement of information technology in information systems is increasing, encouraging the need for solutions to meet the needs of accurate, concise and up-to-date information. Information systems are the main means for the community and various agencies to obtain the necessary information. In the health sector, the Integrated Service Post (Posyandu) is one of the important programs to reduce maternal and infant mortality. Posyandu Melati in Candinata Village, as part of the program, faces challenges in the manual recording of under-five data. The recording process involves a number of complex steps in taking measurements that slow down the dissemination of information to parents of children under five. This study aims to design an information system that can assist cadres in performing their duties, namely recording and processing toddler data. This study proposes the development of a web-based Posyandu information system using the Extreme Programming Method in Candinata Village. Extreme Programming Method was chosen to ensure effective communication, simple coding, and responsiveness to feedback. The results showed that the use of XP successfully designed the system quickly and involved a small team. The results of feature testing using the Black Box Testing method show that the system has been validated and in accordance with the desired needs.